E-tutoring in online training courses - Vegliante, Rosa; De Angelis, Marta (ITALIAN JOURNAL OF EDUCATIONAL RESEARCH, 2019)
Starting from a diachronic analysis regarding the passage from distance education to elearning, the paper aims to analyze the theme of e-tutoring both from a theoretical and a practical point of view. In drawing up a summary of the e-tutoring strategies and possible educational consequences, the advantages derived from the functions performed by the e-tutor in the learning process emerge, which derive from different styles of etutoring. To different pedagogical reference paradigms (behaviorist, constructivist or socio-constructivist), in fact, correspond dissimilar ways of designing e-learning environments, based on instructor centered or learning team centered teaching models. From the analysis carried out, therefore, the crucial role of the e-facilitator emerges, as it greatly affects the training success of the participants, reducing the spatial distance of the online environments and limiting possible e-dropouts.